Sustainable urban development: reality and solutions for infrastructure development - Tran Chung Vinh; Dang Thu Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Vietnam made progress in infrastructure development, but it is still facing many challenges. Urban infrastructure has grown rapidly but unevenly. It causes economic and social imbalance between urban and rural areas. Efforts for sustainable development and adaptability have been attached to special importance, however issues related to management and supervising, environmental issues, climate change and infrastructure safety need to be solved. Sustainable development goals has many different interpretations. This article provides an overview of the actual state of urban infrastructure development in the country related to sustainability through two contents as following: Firstly, it describes the actual state of infrastructure construction and urban development; Secondly, it provides solutions for sustainable development as a necessary condition to achieve sustainable urban infrastructure development. Code: 23081601